1986
DOI: 10.1007/bf00394939
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin in human gastric mucosa and carcinoma

Abstract: The localization of immunoreactive calcitonin (IR-CT) in the human gastric mucosa and tumor tissues was studied using an immunohistochemical peroxidase-antiperoxidase method. A small number of IR-CT-containing cells were observed in both infant and adult gastric antral mucosa and the ratio of IR-CT-containing cells to G cells was about 1:50-100. Moreover, tissue content of IR-CT in normal antral mucosa was 2.37 +/- 0.35 ng/g wet weight. IR-CT-containing cells and G cells decreased with the progress of chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Further analysis will be required to address this possibility. Of interest is that RUNX protein was also found in a few G cells located in the pyloric portion [29]. It is suggested that RUNX3 may play a physiologic role in G cells.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis will be required to address this possibility. Of interest is that RUNX protein was also found in a few G cells located in the pyloric portion [29]. It is suggested that RUNX3 may play a physiologic role in G cells.…”
Section: Discussionmentioning
confidence: 99%
“…MTC tumors frequently arise as a part of the multiple endocrine neoplasia type 2 (MEN2)-syndrome. Calcitonin may also be arisen in some pancreatic endocrine tumors, particularly those that are multi-hormone producing and in some nonendocrine cancers (52).…”
Section: Calcitonin (Ct)mentioning
confidence: 99%
“…Calcitonin may also be raised in some pancreatic endocrine tumours, particularly those that are multihormone producing and in some non-endocrine cancers. 203 The calcitonin family of peptides (includes CGRP, amylin, adrenomedullin and intermedin-I)…”
Section: Calcitonin Assaymentioning
confidence: 99%
“…Calcitonin may also be raised in some pancreatic endocrine tumours, particularly those that are multihormone producing and in some non-endocrine cancers. 203 The calcitonin family of peptides (includes CGRP, amylin, adrenomedullin and intermedin-I) Calcitonin gene-related peptide occurs in two forms: CGRP I (a-CGRP) and CGRP II (b-CGRP) that are encoded by the two calcitonin genes on chromosome 11. 204 CGRP has a widespread distribution in the nervous system.…”
Section: Calcitonin Assaymentioning
confidence: 99%